Simulation of the regularities of physical exercises learning process of boys aged 8 years old - O.V. Ivashchenko; S.S. Iermakov; O.M. Khudolii; T.S. Yermakova; M. Cieślicka; S.V. Harkusha (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: to determine the peculiarities of the formation of motor skills in boys aged 8 years. Materials and methods: In study participated boys of eight years old (n=48). The study used factor experiment plans. The purpose of this experiment was to optimize the modes of education and to determine the peculiarities of the formation of motor skills in boys. Results: Discriminant analysis allowed: to determine the modes of exercise in the formation of motor skills; to answer the question as to how significantly different modes of work on the effectiveness of the formation of motor skills. Established: which of the variables most significantly affect the differentiation of classes; to which class the object belongs based on the values discriminant variables. The influence of the number of approaches, the number of repetitions in the approach and the interval of rest on the level of training for movements is revealed. Conclusions: To choose the most rational mode of exercising in the process of forming motor skills can be used the first discriminating function with an emphasis on the most informative variables.